LEMBAGA SWADAYA MASYARAKAT ALIANSI PEREMPUAN MERANGIN UNTUK KEKERASAN DALAM RUMAH TANGGA - Hamirul Hamirul; Muhammad Nasir (STIE Perbankan Indonesia, 2019)
The recent phenomenon of domestic violence (domestic violence) is increasingly prevalent in Indonesia, including in Merangin district and one of the non-governmental organizations that handles this is the NGO Merangin Women's Alliance (APM) which is involved in this and with descriptive research methods with qualitative approaches, data the results of his research are the Participation of Non-Governmental Organizations Alliance of Women in Overcoming Domestic Violence by conducting consultation and assistance services for Victims of Violence Against Women and Children through counseling conducted in each village in the APM region that is tailored to the situation and conditions participate in socializing Law Number 23 of 2004 concerning the Elimination of Domestic Violence (PKDRT).